Update on the Canadian Institutes of Health Research: Where Will Respiratory Health Research Fit in? - Malcolm King (Canadian Respiratory Journal)
My main focus as Canadian Thoracic Society (CTS) President has been on research. The centre of attention has, of course, been the soon-to-be-established Canadian Institutes of Health Research (CIHR) and our Society's efforts to establish a position for respiratory research withing this new organization.